Factors Associated with Adherence to Antihypertensive Therapy amongst OPD Attendants of the Tema General Hospital. - Amoako – Adusei, A. (University Of Ghana, 2019)
Background: Cardiovascular related diseases and its deaths have increased over the years with hypertension being a precursor to these diseases. Proper management of the condition has proven to increase the life expectancy of patients. Adherence appears to be one of the important factors that influence the outcome of therapy greatly. Poor medication adherence is associated with poor disease outcomes, waste of health care resources and contributes to reduced blood pressure control. Objectives: This study sought to determine the level of adherence and the factors associated with adherence to antihypertensive therapy OPD attendants of the Tema General Hospital Method: A hospital-based cross-sectional study was carried out at the Tema General Hospital. Patients who have been on antihypertensive medication for more than a month and aged 18 years and above were randomly sampled from among OPD attendants on daily basis. Data were collected using a structured questionnaire based on the eight-item Morisky scale of medication adherence to determine their level of adherence to treatment. Factors likely to influence adherence was elicited from the patients. Data collected were analyzed using STATA version 15.0. Descriptive statistics was done for all the socio-demographic characteristics of respondents. A Chi-squared test was used to test for association between adherence to anti-hypertensive medication and all the independent variables. The magnitude and strength of the association was determined for each variable and anti-hypertensive medication adherence by a simple logistics regression analysis. Multiple logistics model was used to determine factors influencing hypertensive medication adherence after adjusting for confounders. Results: Out of the 342 participants who took part in this study (age range 28-95years, mean age 55.10 + 10.42), 13.16% had medium level of adherence and 86.84% had low level of adherence. The cost of therapy was the single challenge most of the participants faced with regards to adherence and diabetes was the most common co-morbidity amongst the participants. After adjusting for confounders, the odds ratio and confidence interval of factors that were significantly associated with medium level of adherence to antihypertensive medication were acceptability of waiting time at the hospital 0.04 (0.01 – 0.23) and difficulty in reaching the hospital 3.52 (1.50 – 8.27). Conclusion: The level of adherence amongst residents in the Tema General Hospital was thirteen percent which represents only medium level of adherence. Acceptability of waiting time at the hospital and difficulty in reaching the hospital were the factors significantly associated with adherence.
MPH.
Keywords: Hypertension; Cardiovascular Disease; Tema General Hospital; Healthcare System